Identification of violence in the hospital environment: perceptions of nurses - M. Mnif; N. Smaoui; R. Feki; I. Gassara; S. Omri; N. Charfi; J. Ben Thabet; L. Zouari; M. Maalej; M. Maalej (European Psychiatry, 2022)
Introduction Violence is recognised by the WHO as a major and ubiquitous public health problem, that is constantly worsening.